ON THE USE OF DATA IN FAVOR OF POLITICAL INCLUSION: GENDER IDENTITY AND SEXUAL ORIENTATION IN PARTY LEADERSHIP - Alcântara, Adriana Soares; Perez, Olivia Cristina (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
This article investigates the absence of data regarding gender, gender identity, and sexual orientation of individuals who comprise party leadership. The objective is to highlight the gaps found in the information provided by the Electoral Court and propose improvements to the Electoral Court system, to be implemented by political parties. This research is innovative in that it presents the flaws and suggests improvements to reduce inequality in the participation of politically marginalized groups, with a focus on the transgender population. Theories from gender studies and open data from the Electoral Court, collected from the TSE website, were used, as found on the Election Statistics page and in the subgroups of Candidacy Statistics, Profile, and Candidacy Status. Cross-referencing was done based on territorial coverage, gender, and gender identity. The results point to the need for connection between the systems managed by the Electoral Court based on information provided by political parties and the electorate in voter registration campaigns. Finally, we present suggestions for improvement in specific Electoral Court systems.